(untitled) (Kathmandu University Medical Journal, 2014)
The synchronous occurrence of primary renal cell carcinoma with gastric cancer is very rare. We report a case of 41 year old male who presented on 05/07/2011 to M S Ramaiah hospital, Bangalore with history of fever, pain abdomen and malena. Ultrasound abdomen and pelvis showed large heterogenous mass arising from the upper pole of left kidney. Computed tomography of the abdomen showed left renal cell carcinoma. Renal biopsy showed features consistent with renal cell carcinoma – clear cell type. Oesophagogastroduodenoscopy revealed gastric polypoidal growth. Gastric biopsy from the growth revealed poorly differentiated adenocarcinoma of stomach. We report this case to highlight a rare occurrence of synchronous malignancy of stomach and kidney. DOI: http://dx.doi.org/10.3126/kumj.v11i1.11053 Kathmandu University Medical Journal Vol.11(1) 2013: 94-95